2006
DOI: 10.1021/ic061198c
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Properties of [−O−BiIII...OMo−]nChains

Abstract: A coordination polymer [Cp(O)2Mo-O-Bi(o-tolyl)2]n, II, containing Mo-O-Bi and Mo=O...Bi moieties was investigated with respect to its behavior in contact with OH- and Cp2MoH2 and as potential single source precursor in the polyol method. It turned out that hydroxide as a base breaks up the polymer to yield CpMoO3- and (o-tolyl)2BiOH. The latter polymerizes to give the coordination polymer [(o-tolyl)2BiOH]n, 1. Alternatively, 1 can be prepared by reacting [(o-tolyl)2Bi(hmpa)2]SO3CF3 with NBu4OH/H2O in thf/water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…8 The 5,6,7,12‐tetrahydrodibenz[c,f][1,5]azabismocine framework is highly stable as a diorganobismuth fragment and, therefore, is suitable for the study of diorganobismuth compounds bearing various heteroatom groups on the bismuth atom. Since structural and reactivity studies of diorganobismuth(III) hydroxides,5, 9 oxides,5, 9, 10 and alkoxides9, 11 are limited, we examined the synthesis of such compounds with the 5,6,7,12‐tetrahydrodibenz[c,f][1,5]azabismocine framework. In analogy to the synthesis of {(2,4,6‐Me 3 C 6 H 2 ) 2 Bi} 2 O 2 ,10d bismuth chloride 3 was treated with aqueous sodium hydroxide solution, and subsequent recrystallization of the crude product from toluene under nitrogen exclusively afforded bismuth oxide 6 .…”
Section: Methodsmentioning
confidence: 99%
“…8 The 5,6,7,12‐tetrahydrodibenz[c,f][1,5]azabismocine framework is highly stable as a diorganobismuth fragment and, therefore, is suitable for the study of diorganobismuth compounds bearing various heteroatom groups on the bismuth atom. Since structural and reactivity studies of diorganobismuth(III) hydroxides,5, 9 oxides,5, 9, 10 and alkoxides9, 11 are limited, we examined the synthesis of such compounds with the 5,6,7,12‐tetrahydrodibenz[c,f][1,5]azabismocine framework. In analogy to the synthesis of {(2,4,6‐Me 3 C 6 H 2 ) 2 Bi} 2 O 2 ,10d bismuth chloride 3 was treated with aqueous sodium hydroxide solution, and subsequent recrystallization of the crude product from toluene under nitrogen exclusively afforded bismuth oxide 6 .…”
Section: Methodsmentioning
confidence: 99%
“…[7,8] The 5,6,7,12-tetrahydrodibenz[c,f]-[1,5]azabismocine framework is highly stable as a diorganobismuth fragment and, therefore, is suitable for the study of diorganobismuth compounds bearing various heteroatom groups on the bismuth atom. Since structural and reactivity studies of diorganobismuth(III) hydroxides, [5,9] oxides, [5,9,10] and alkoxides [9,11] are limited, we examined the synthesis of such compounds with the 5,6,7,12-tetrahydrodibenz[c,f]-[1,5]azabismocine framework. In analogy to the synthesis of {(2,4,6-Me 3 C 6 H 2 ) 2 Bi} 2 O 2, [10d] bismuth chloride 3 was treated with aqueous sodium hydroxide solution, and subsequent recrystallization of the crude product from toluene under nitrogen exclusively afforded bismuth oxide 6.…”
mentioning
confidence: 99%
“…The molecular structure is shown in Figure . Besides {(mes) 2 Bi} 2 O, (mes = 1,3,5‐trimethylbenzyl) and {( o ‐tolyl) 2 Bi} 2 O, 1 is only the third bismuth containing compound with a [Bi–O–Bi] motif, the molecular structure of which was determined. Two [(Cp 2 Re) 2 Bi] units are connected by an oxygen atom to form a bent [Bi–O–Bi] entity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore the oxidation of primary and secondary alcohols with [( o ‐ans) 3 BiO] 2 ( o ‐ans = 2‐anisole) led to the formation of the side product {( o ‐ans) 2 Bi} 2 O and the oxidation of tetraorganodibismuthanes R 2 Bi‐Bi R 2 with dioxygen was found to lead to {(mes) 2 Bi} 2 O as a side product, which could be analyzed by means of X‐ray diffraction , . In previous work we have shown that the oxide [( o ‐tolyl) 2 BiOBi( o ‐tolyl) 2 ] ( V ) and the polymeric hydroxide [( o ‐tolyl) 2 BiOH] n ( VI ) form via the hydroxide IV in thf / water solutions (Scheme ) . Hence, the formation of 1 in mixtures of [Cp 2 ReH] ( I ), [Bi(O t Bu) 3 ] and [{Cp 2 Re} 2 Bi(O t Bu)] ( II ) / [CpRe( μ ‐ η 5 , η 1 ‐C 5 H 4 )Bi–ReCp 2 ] ( III ) was conceivable to have taken place due to the presence of H 2 O (in commercially available C 6 D 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation